The Ethnohistory of Freshwater Use on Rapa Nui (Easter Island, Chile) - Hixon, Sean; DiNapoli, Robert J.; Lipo, Carl P.; Hunt, Terry L. (Waka Kuaka, 2019)
Sources of drinking water on islands often present critical constraints to human habitation. On Rapa Nui (Easter Island, Chile), there is remarkably little surface fresh water due to the nature of the island’s volcanic geology. While several lakes exist in volcanic craters, most rainwater quickly passes into the subsurface and emerges at coastal springs. Nevertheless, the island sustained a relatively large human population for hundreds of years, one that built an impressive array of monumental platforms (ahu) and statues (moai). To understand how Rapanui acquired their scarce fresh water, we review ethnohistoric data from first European arrival (1722) through the mid-twentieth century. Ethnohistoric accounts identify a diversity of freshwater sources and describe various Rapanui freshwater management strategies. Our findings highlight the importance of coastal freshwater seeps and provide much-needed insight into how Rapanui procured this vital and necessary resource.